Preliminary results of linac-based radiosurgery in arteriovenous malformations and cerebral tumours in the Oncology Centre in Bydgoszcz - Sokal, Paweł; Lebioda, Andrzej; Harat, Maciej; Furtak, Jacek; Grzela, Monika; Kabacińska, Renata; Makarewicz, Roman; Zieliński, Piotr; Windorbska, Wiesława (Contemporary Oncology/Współczesna Onkologia, 2013)
Aim of the study: Efficacy of stereotactic radiosurgery (SRS) in the treatment in cerebral AVM’s, mennigiomas, metastases, acoustic neuromas and recurrent anaplastic gliomas is well documented. The object of this work was the analysis of the results of the treatment of AVM and selected cerebral lesions with linear accelerator-based stereotactic radiosurgery. Material and methods : The lesions included: 12 AVMs, 2 cavernomas, 27 meningiomas, 16 metastases, 5 acoustic neuromas, 16 gliomas in 78 patients. A mean radiation dose of 16Gy was delivered to the tumour or AVM margin and 12Gy to the tumours located in a ponto-cerebellar angle. Follow-up was 18 months. Results : Control of tumour growth or AVM was achieved in all cases after 6 months and radiological regression was observed in 20 cases after 12 months. The best results were noted in AVM's, meningiomas and neuromas.There were no new permanent deficits nor complications after radiosurgery requiring medicamentation. Conclusions : Organization of SRS in Oncological Center in Bydgoszcz involving close co-operation of radiotherapist, neurosurgeon and physicist in the process of qualification and treatment planning is based on the best global standards. Preliminary results of treatment are consistent with the literature data. A longer follow-up is required to determine the long term efficacy and the toxicity of this treatment in our institution.